If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 16 + -3x = 12 + -6x + -6 Reorder the terms: 16 + 7x + -3x = 12 + -6x + -6 Combine like terms: 7x + -3x = 4x 16 + 4x = 12 + -6x + -6 Reorder the terms: 16 + 4x = 12 + -6 + -6x Combine like terms: 12 + -6 = 6 16 + 4x = 6 + -6x Solving 16 + 4x = 6 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 16 + 4x + 6x = 6 + -6x + 6x Combine like terms: 4x + 6x = 10x 16 + 10x = 6 + -6x + 6x Combine like terms: -6x + 6x = 0 16 + 10x = 6 + 0 16 + 10x = 6 Add '-16' to each side of the equation. 16 + -16 + 10x = 6 + -16 Combine like terms: 16 + -16 = 0 0 + 10x = 6 + -16 10x = 6 + -16 Combine like terms: 6 + -16 = -10 10x = -10 Divide each side by '10'. x = -1 Simplifying x = -1
| 6x+y=8 | | S=3(r^3)t | | p-5=-12+p | | S=3r^3t | | 2a-5+12c=2a+b | | 5z-12=5z+15 | | (13x-25)+(9x+3)=77 | | -100x=10x^2 | | (0.1x+1)*.1x=2x | | -5(t-1)+9t=7t-6 | | 83=x+59 | | 63-n=15 | | 7+5b=37 | | 42-5=x | | 6+3+c=19 | | (5x-6)+(2x+5)=180 | | 17-x=16-5 | | 37-12=c-5 | | 6+2+n=19 | | 56=x-7 | | -.3y+.1=.5 | | 50-t^2=0 | | 3x+6y=39 | | 9z-z=-1+6z-3-2 | | h=-16t^2+144 | | 5-2x=3x-1 | | 11y+2=10y-4 | | 2x-7=-7+5x | | -3+2x=-6x-91 | | 3x+7=6x-20 | | -7x-10=90+3x | | 2x+7=31+4x |